The glacial geomorphology of upper Godthabsfjord (Nuup Kangerlua) in southwest Greenland - Pearce, Danni M.; Mair, Douglas W. F.; Rea, Brice R.; Lea, James M.; Schofield, J. Edward; Kamenos, Nicholas A.; Schoenrock, Kathryn (Journal of Maps, 2018)
The Greenland Ice Sheet (GrIS) is known to have experienced widespread retreat over the last century. Information on outlet glacier dynamics, prior to this, are limited due to both a lack of observations and a paucity of mapped or mappable deglacial evidence which restricts our understanding of centennial tomillennial timescale dynamics of the GrIS. Here we present glacial geomorphological mapping, for upper Godthabsfjord, covering 5800km(2) at a scale of 1:92,000, using a combination of ASTER GDEM V2, a medium-resolution DEM (error <10m horizontal and <6m vertical accuracy), panchromatic orthophotographs and ground truthing. This work provides a detailed geomorphological assessment for the area, compiled as a single map, comprising of moraines, meltwater channels, streamlined bedrock, sediment lineations, ice-dammed lakes, trimlines, terraces, gullied sediment and marine limits. Whilst some of the landforms have been previously identified, the new information presented here improves our understanding of ice margin behaviour and can be used for future numerical modelling and landform dating programmes.Data also form the basis for palaeoglaciological reconstructions and contribute towards understanding of the centennial to millennial timescale record of this sector of the GrIS.